Unsteady aerodynamics of flexible wings in transverse gusts. (January 2022) - Fernandez, Fidel; Cleaver, David; Gursul, Ismet
Abstract: Unsteady aerodynamics of two flexible cantilevered wings in transverse gusts has been studied by means of force, velocity, and deformation measurements. The first bending frequencies of the wings were in the range of gust frequencies tested. The deformation measurements revealed that plunge angle due to the bending deflections is generally small. However, it becomes large at the resonant conditions and significantly attenuates the amplitude of the effective gust angle perceived by the wing, although the unsteady lift is difficult to measure accurately for the resonant cases. As the gust frequency increases, the more flexible wing experiences more separated flow during the cycle. Nevertheless, for both flexible wings, the lift amplitude normalized by the gust amplitude is smaller than those of the rigid wings with separated flows. When the maximum effective angle of attack is smaller than a critical value, the lift amplitude normalized by the gust amplitude is close to the theoretical predictions for attached flows and the effect of the gust reduced frequency is small. In contrast, above the critical value of the maximum effective angle of attack, the normalized lift can be amplified or attenuated, depending on the gust reduced frequency.